(untitled) (Research, Society and Development, 2025)
Introduction: Caregivers of children with Neurodevelopmental Disorders (NDDs) experience a multidimensional burden that affects their physical, emotional, social, and financial well-being. This burden is intensified in contexts marked by social vulnerability, limited specialized services, and persistent stigma. Symptom severity — such as autism, intellectual disabilities, and complex comorbidities — further increases caregiving demands. This article aims to discuss the nature of caregiver burden among parents of children with NDDs, examining the factors that shape it and the intervention strategies suggested in recent literature. Methods: An integrative literature review was conducted following a structured methodological framework. Articles published between 2015 and 2025 were identified in PubMed using descriptors related to caregiver burden and neurodevelopmental disorders. Results: Eighteen studies met the inclusion criteria. Findings consistently indicated high levels of psychological distress, fatigue, sleep disturbances, and social isolation among caregivers. Interventions such as telehealth, peer support, and family-centered practices demonstrated positive outcomes in reducing stress and strengthening resilience. Discussion: The analysis shows that caregiver burden arises not only from clinical demands but also from structural factors, including inequitable access to services and insufficient public policies. Resilience-promoting strategies and multiprofessional support can mitigate these effects, but they remain underutilized in underserved settings. Conclusion: Caregiver burden represents a significant public-health concern requiring intersectoral action. Strengthening inclusive policies, expanding access to specialized and telehealth services, and improving professional training are essential to support caregivers and promote better developmental outcomes for children with neurodevelopmental disorders.